A forbidden alchemy - McEwan, Stacey (McEwan, Stacey. Alchemy, 2025)
"This stunning slow-burn romantasy follows a fated pair who uncover a world-changing secret and are thrust into a violent class war, navigating love, loss, and devastating betrayals. Nina Harrow and Patrick Colson are twelve years old when they are whisked away from the shadows of their disenfranchised mining towns to dazzling Belavere City to discover their magical potential. Those who pass Belavere's test will become Artisans, wielders of powerful elemental magic destined to fulfill the city's grand ambitions. For Nina, the Artisan School symbolizes a dream and an escape from her harsh reality, while Patrick yearns to return to his Craftsman family, whose extraordinary physical strength serves the idium mines keeping the city alive. And then they uncover a devastating truth: Artisans aren't born, they're chosen. They part ways on very different paths, leaving them to carry the burden of this secret alone. In the years that follow, a Craftsman revolution ignites, thrusting Nina and Patrick into opposing factions of a brewing war. Now an elite Artisan with the very rare talent for charming earth, Nina has turned her back on the fight, haunted by the loss of her found family. But fate intervenes when she is captured by Patrick's rebel group. Despite the years and conflict that separates them, Patrick hasn't forgotten Nina. He desperately seeks her help for a mission that could shift the tides against Belavere City. Reluctantly, she agrees, battling the sparks flying between them. But when Nina's first love reappears, asking her to betray Patrick for the sake of the Artisans, Nina faces an impossible choice that could alter the fate of their world"--